Menyelami Makna dalam Kata: Diksi dan Adaptasi Budaya Tokoh dalam Surat untuk Jenaka Karya Gigrey - Afifah, Sundus; Cempaka Harum, Alexandria (P3M Politeknik Negeri Media Kreatif, 2025)
This research aims to determine the use of diction in Surat untuk Jenaka by Gigrey as a representation of intercultural communication. This novel presents interactions between characters from different cultural and time periods: the colonial (1923) and modern Indonesian period (2019). The research method used is descriptive qualitative with content analysis technique. The focus of the research includes the use of foreign, connotative, and concrete diction that represents intercultural communication dynamics. The results show that the diction in the novel functions not only as an aesthetic element but also as a cultural accommodation strategy. Foreign diction reflects social status, Western culture influence, and is used as a form of convergence to build closeness between characters. Connotative diction reinforces cultural values-social norms, such as gender relations, hierarchy, serving as a means of social criticism. Diction concretely clarifies social roles, boundaries, and relationships between characters within the described cultural context.